Main anthraquinone components in Aloe vera and their inhibitory effects on the formation of advanced glycation end‐products. Issue 5 (27th December 2016) - Kang, Shimo; Zhao, Xin; Yue, Lu; Liu, Ling
Abstract: Food heating process causes increased protein glycation and the formation of advanced glycation endproducts (AGEs) which related with diabetes and ageing. Aloe vera ( A. vera ) extract is a potent antioxidant with established effects attributed largely to a key ingredient anthraquinone. This study investigated the inhibitory ability of the three anthraquinones from A. vera on the formation of AGEs in a heated model system at 70°C. Anthraquinones, including aloe‐emodin (AED), emodin (ED), and chrysophanol (CSN), were extracted from A. vera and analyzed by ultra‐high performance liquid chromatography‐tandem mass spectrometry. Under optimal extraction conditions, the extraction yield of the anthraquinones was 4.377 mg/g. Anthraquinones showed good inhibition toward the formation of glycation products; the inhibition rates of AED, ED, and CSN on crosslinked AGEs were 46.48%, 66.38%, and 57.32% at 10 μM concentrations. Sodium dodecyl sulfate–polyacrylamide gel electrophoresis images also proved that the anthraquinones could significantly inhibit crosslinked AGE formation in a time‐dependent manner. ED showed higher inhibitory ability than AED and CSN on the formation of N ɛ ‐(carboxymethyl)lysine and crosslinked AGEs. The results indicate that the antiglycation properties of these anthraquinones are likely related to the phenolic hydroxyl groups in their structures, but this ability is not related to their antioxidant activity, which probably depends on the whole structure of the quinone. Generally, the anthraquinones in A. vera, especially ED, can effectively inhibit AGE formation and reduce protein crosslinking during food processing, even at low concentration. Practical applications: The inhibitory effects of three anthraquinones extracted from Aloe vera on the formation of AGEs were investigated in a heated model system. The results indicate Aloe can be used as an effective inhibitor of glycation products in food processing, moreover, this research can be useful for finding suitable nature inhibitors of AGEs for food processing.